PENINGKATAN MOTIVASI KEWIRAUSAHAAN SISWA AGRIBISNIS PERIKANAN MELALUI IMPLEMENTASI SISTEM TEKNOLOGI AKUAKULTUR GREEN WATER, BIOFOK DAN AQUAPONIK DI SMK UNGGUL NEGERI 2 BANYUASIN III - Rizki, Rani Ria; Puteri, Rizki Eka; Oktavianti, Santi; Arafah, Elmeizy; Guttifera; Lestary, Siti; Prariska, Donny; Triesia, Diah; Sari, Selly Ratna (Universitas Mataram, 2025)
SMK Unggul Negeri 2 Banyuasin III, established in 2014, focuses on developing agribusiness, plantation, and fisheries skills to support the abundant natural resources in Banyuasin Regency. However, the limited practical facilities and the shortage of teachers with a fisheries background have resulted in suboptimal learning. This situation affects graduates' ability to master field skills and entrepreneurship that meet job market demands. This community service aims to enhance students' entrepreneurship through eco-friendly technologies, such as green water, bioflok, and aquaponics, for efficient and sustainable cultivation while reducing operational costs. The methods used in this service include the socialization of green water, bioflok, and aquaponics technologies, practical training in cultivation and entrepreneurship, implementation of eco-friendly technologies, as well as mentoring and evaluation. The sustainability of the program is maintained through monitoring of facilities, cultivation results, and marketing strategies. The results of the service show an improvement in students' knowledge and skills in modern aquaculture through Green Water, Bioflok, and Aquaponics technologies. The training successfully provided a deeper understanding of cultivation system principles, water quality management, and fish maintenance. Additionally, students gained skills in business analysis and marketing strategies for cultivation products. This program also increased students' entrepreneurial motivation to start sustainable fish farming businesses. This service successfully enhanced students' field skills and entrepreneurship, enabling them to compete according to job market needs. The program not only improved students' technical skills in fisheries and agriculture but also fostered an entrepreneurial mindset focused on sustainability and economic independence.